Vibration Control of an Industrial Moving Strip in the Presence of Input Deadzone - He, Wei; He, Xiuyu; Sun, Changyin (IEEE transactions on industrial electronics (1982), 2017)
This paper investigates the boundary control design and the stability analysis for an axially moving strip system under the external time-varying disturbances. Based on the infinite dimensional dynamical model, the active control strategies are acted on the boundary of the system to deal with the problems of vibration suppression and nonlinear deadzone input characteristic. In addition, a disturbance observer is constructed to handle the bounded and uncertain boundary disturbance. With the proposed boundary control laws, the states of the moving strip system are proven to converge to a neighbourhood of the equilibrium points, namely, the stability of the moving strip system can be guaranteed. Through comparing the simulation results, the effectiveness of the boundary control law is verified.